可塑性グラウト材及びそれを用いて行う止水工法 (2018)
PROBLEM TO BE SOLVED: To provide a plastic grout material and a water cutoff construction method therewith which can show enough water cutoff effect under severe environment conditions with flowing water of high flow rate or high temperature that conventional well-known plastic grout materials is difficult to cutoff water enough.SOLUTION: In a plastic grout material, a main material cement contained in a cement milk material is low heat Portland cement, fly ash contained in the cement milk material is reformed fly ash which is a high quality fly ash equivalent of Japanese industrial standard II class, and underwater inseparable chemical admixture contained in the cement milk material is acrylic amide-2-methylpropanesulfonic acid based thickening agent.SELECTED DRAWING: None